Analisa Perilaku Keamanan Informasi Pengguna Mobile Banking - Sembiring, Sintaria; Pandia, Henry (TeIKa, 2024)
The use of mobile banking services has grown rapidly and revolutionized the banking sector, offering customers convenient and efficient access to banking services without time and distance limitations. However, this convenience comes with information security risks. Therefore, user information security behavior is crucial to minimize these risks and their impacts. This study aims to analyze the information security behaviors of mobile banking users in Indonesia, focusing on the factors that influence these behaviors. This research surveyed 365 respondents who use mobile banking applications, with diverse genders, ages, education levels, and mobile banking application preferences. The study measured five dimensions of information security behavior: password management, messaging app usage, internet usage, devices usage in public, and incident reporting. The research found that information security behaviors among mobile banking users vary significantly. These findings highlight the importance of banks integrating user behaviors into comprehensive information security strategies. This study contributes to enhancing information security practices in mobile banking by providing insights into user behaviors and demographic influences.